2018
DOI: 10.1029/2018gc007936
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Petrological and Geophysical Constraints on Magma System Architecture in the Western Galápagos Archipelago: Insights From Wolf Volcano

Abstract: The 2015 eruption of Wolf volcano was one of the largest eruptions in the Galápagos Islands since the onset of routine satellite‐based volcano monitoring. It therefore provides an excellent opportunity to combine geophysical and petrological data, to place detailed constraints on the architecture and dynamics of subvolcanic systems in the western archipelago. We present new geodetic models that show that pre‐eruptive inflation at Wolf was caused by magma accumulation in a shallow flat‐topped reservoir at ~1.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
3
2
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(91 citation statements)
references
References 86 publications
7
83
1
Order By: Relevance
“…The 2‐ to 3‐km depth of the sills centroids in our study is also consistent with the depth of the source that caused the subsidence of the southern part of the caldera from 1997 to 2001 (Hooper et al, ). Furthermore, this depth agrees with that of the top of the shallow magmatic systems of the nearby calderas at Fernandina, Sierra Negra, and Wolf (from 1 to 3 km depth below the caldera; Bagnardi et al, ; Jónsson, ; Stock et al, ). Such depths are more consistent with those of magmatic sources than with that of the shallow hydrothermal system of Alcedo.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The 2‐ to 3‐km depth of the sills centroids in our study is also consistent with the depth of the source that caused the subsidence of the southern part of the caldera from 1997 to 2001 (Hooper et al, ). Furthermore, this depth agrees with that of the top of the shallow magmatic systems of the nearby calderas at Fernandina, Sierra Negra, and Wolf (from 1 to 3 km depth below the caldera; Bagnardi et al, ; Jónsson, ; Stock et al, ). Such depths are more consistent with those of magmatic sources than with that of the shallow hydrothermal system of Alcedo.…”
Section: Discussionsupporting
confidence: 71%
“…Successively, between 1997 and 2001, uplift switched to subsidence (<11 cm), which has been interpreted as deflation of an ellipsoid‐like body at ~2.2 km below sea level (Hooper et al, ). Conversely to Cerro Azul, Fernandina, and Wolf (Amelung et al, ; Bagnardi et al, ; Stock et al, ; Xu et al, ), no deformation is recorded outside the caldera of Alcedo in the last 30 years.…”
Section: Geological Background: Galápagos and Alcedomentioning
confidence: 95%
“…2; ref. 19 ; Supplementary Dataset 1). These do not show any significant compositional variability outside of uncertainty, despite sampling lava flows that erupted at different times through the circumferential fissure phase of the eruption.…”
Section: Resultsmentioning
confidence: 99%
“…Recent Galápagos eruptions have afforded geophysical constraints on magma storage depths 19,21,32,33 , making them good targets for understanding the processes responsible for 71 . The sampling locations of the lavas and tephra analysed in this study are shown as green circles and blue diamonds, respectively.…”
mentioning
confidence: 99%
“…Mollo and Hammer, 2017) is always necessary for the crystals to grow to the size of phenocrysts. In natural volcanic rocks, augite crystals often deviate from the frequently assumed 'treering' model and develop sector zoning (Hollister and Gancarz, 1971;Arculus, 1973;Ferguson, 1973;Downes, 1974;Leung, 1974;Dowty, 1976;Duncan and Preston, 1980;Shimizu, 1981;Watson and Liang, 1995;Brophy et al, 1999;Hammer et al, 2016;Welsch et al, 2016;Neave and Putirka, 2017;Mollo and Hammer, 2017;Stock et al, 2018), generating an hourglass form ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%